THE EFFECT OF MAGNETIC FIELD ON ANTIBIOTIC INHIBITION FOR Escherichia coli AND Bacillus sp. - Sumardi, Sumardi; Agustrina, Rochmah; Ekowati, Christina Nugroho; Putra, Rizani Oktanisyah; Hartono, Madi (Jurnal Kedokteran Hewan, 2019)
This study was aimed to test the growth of bacteria Escherichia coli (E. coli) and Bacillus sp. which were exposed to magnetic fields. In the first stage of the study, the effect of magnetic fields on the growth of E. coli and Bacillus sp were observed. The futher study was aimed to evaluate the effect of magnetic field on antibiotic sensitivity againts the growth of E. coli and Bacillus sp. The magnetic fields treatments were 0.0 mT (control), 0.1 mT, 0.2 mT, 0.3 mT which were exposed for 10 hours for each treatment. Five antibiotics (trimethoprim, ampicillin, nalidixic acid, streptomycin and chloramphenicol) were used for each bacteria. The result showed that the magnetic field did not influence the colony growth of E.coli, but in Bacillus sp. was seen the increasing of colony area in magnetic field of 0.1 mT and 0.2 mT compared with control treatment. Antibiotic of trimethoprim, nalidixic acid, and ampicillin increase the growth inhibition of E. coli when the bacteria have been exposed to 0.1 mT; 0.2 mT; 0.3 mT magnetic field for 10 minutes. The inhibition by streptomycin and chloramphenicol antibiotic on E. coli did not affected by magnetic field exposure. The inhibition of Bacillus sp by trimethoprim and ampicillin increased when the bacteria have been exposed to 0.2 mT and 0.3 mT magnetic field for 10 minutes. The inhibition of nalidixic acid, streptomycin and chloramphenicol to Bacillus sp. did not affected by the magnetic field exposure.